2013
DOI: 10.11604/pamj.2013.15.128.2702
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of spontaneous bacterial peritonitis in liver cirrhosis with ascites

Abstract: IntroductionSpontaneous bacterial peritonitis (SBP) is a common bacterial infection in patients with cirrhosis and ascites requiring prompt recognition and treatment. The aim of this study was to determine the prevalence, and characteristics of SBP among in-patients with cirrhosis and ascites seen at our facility.MethodsThirty one patients with liver cirrhosis and ascites who were admitted into the Medical ward of the Ekiti State University Teaching Hospital (EKSUTH), Ado-Ekiti, Nigeria from August 2009 to Jul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
20
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 30 publications
5
20
2
Order By: Relevance
“…Bibi et al 17 from Karachi reported E.coli in 63.5 % SBP cases having liver cirrhosis which is close to our study results. Oladimeji et al 16 also reported 70 % E. coli predominating among causative organisms of SBP which is close to our findings.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Bibi et al 17 from Karachi reported E.coli in 63.5 % SBP cases having liver cirrhosis which is close to our study results. Oladimeji et al 16 also reported 70 % E. coli predominating among causative organisms of SBP which is close to our findings.…”
Section: Discussionsupporting
confidence: 92%
“…A study by Sheikhbahaie et al 15 also reported male gender predominance with male: female ratio was 1.25:1 which is in compliance with our study results. Oladimeji et al 16 also reported male gender predominance with 54.8%. In our study, E.coli was noted in 135 (73.8%), Staph.…”
Section: Discussionmentioning
confidence: 89%
“…In an Egyptian prospective cohort, the burden of GPB turned out to be as high as 73.2%, namely 30 out of 41 episodes, including 10 cases by Listeria monocytogenes [ 23 ]. In contrast, a retrospective study conducted in Nigeria, which reviewed medical records from August 2009 to July 2010, showed a much smaller proportion of GBP, which although not marginal was equal to 31.8% (7/22)[ 24 ].…”
Section: Epidemiology Of Sbp: Change Of Paradigmmentioning
confidence: 99%
“…15 Despite an improvement in patient care, mortality after a single episode of SBP is estimated to be 32.5% at 1 month and 66.2% after 1 year. 16 Without prophylactic antibiotics; two-thirds of these patients have recurrences of infection within 12 months. 17 Patients of cirrhosis with higher serum bilirubin, Child-Pugh stage C, and thrombocytopenia are more likely to develop SBP.…”
Section: Discussionmentioning
confidence: 99%